DELINEATION OF GROUNDWATER POTENTIAL ZONES IN KADUNA METROPOLIS, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
The scarcity of potable surface water in the Kaduna metropolis has resulted in a high dependence on reliable fresh groundwater. This has led to an increasing drilling of boreholes some of which have failed due to poor groundwater prospecting before drilling.  The main aim of this study is to delineate the groundwater potential zones in Kaduna metropolis. The factors considered for this were lineament, drainage, elevation, slope, rainfall, soil, land use/ land cover and geology. Thematic maps for each of these factors were generated and the Analytical Hierarchical Process (AHP) was used to weight the various factors according to their influence on the occurrence of groundwater in the study area. The weighted index overlay was carried out and the groundwater potential map produced was classified into; very low, low, moderate and high groundwater potential zones covering 29.4%, 36.13%, 25.55% and 8.88% of the study area respectively. The results showed that lineament density and drainage density with weight percentages of 27% and 22% respectively were the major contributing factors towards the occurrence of groundwater in the study area. Rainfall and land use/ land cover with 4% each were the least contributing factors. The high groundwater potential zone was spread all round the study area but occurred mostly in the northern part of Kaduna metropolis. It was seen that the northern part of the metropolis had the best groundwater potential and would be the most suitable location for the exploitation of potable water for urban use
Keywords: Groundwater, Groundwater potential zones, Weight, Analytical Hierarchical Process